Rhein functionalized magnetic chitosan as a selective solid phase extraction for determination isoflavones in soymilk. (1st June 2017) - Guo, Hui; Xue, Lu; Yao, Shen; Cai, Xiaohua; Qian, Junqing
Highlights: A new solid-phase extraction mode was developed for separation some flavones from the complex interference system. Rhein anchored on magnetic chitosan microparticles was used as sorbents for the extraction of target analytes. The magnetic microparticles could be prepared facilely without removal of the template molecule. This kind of magnetic microparticles was particularly suitable for fast determination and quanlitification of isoflavones in soymilk. Abstract: A new solid-phase extraction mode was developed for separation some flavones from the complex interference system. In the experiment, rhein anchored on magnetic chitosan microparticles, prepared facilely without removal of the template molecule, was used as sorbents for the extraction of target analytes; after completion of the extraction process, Fe3 O4 particles acted as carrier to retrieve rhein functionalized magnetic chitosan microparticles (RMCMPs) from the sample solution. RMCMPs showed excellent selective adsorption capacity of isoflavones. The result suggested that the method was useful for fast determination and quantification of isoflavones in soymilk. The RMCMPs were characterized by scanning electron microscope (SEM), X-ray diffraction (XRD) and Fourier transforms infrared spectrometer (FTIR).